2021
DOI: 10.1002/rmv.2248
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of Covid‐19‐A literature review

Abstract: Summary Initially, it was reported that coronavirus 2019 disease (Covid‐19) affects respiratory, gastrointestinal and neurological systems, but the oral, olfactory and integumentary systems are also involved. This review discusses various oral manifestations of Covid‐19 reported in the literature along with possible underlying mechanisms. The reported manifestations include taste impairment, oral mucosal changes (petechiae, ulcers, plaque‐like lesions, reactivation of herpes simplex virus 1(HSV1), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 40 publications
6
68
0
8
Order By: Relevance
“…In the present report, a large ulcer was also found on Cat-1's tongue base at the time of presentation, which may have contributed to inappetence. Various oral manifestations of COVID-19 have been reported in human patients, including dry mouth, gustatory impairment, gingivitis, sialadenitis, vesicular and ulcerative mucosal lesions predominantly located on dorsal surface of the tongue (as in our case), hard palate, and labial mucosa ( 45 47 ). The exact pathogenesis of such oral signs remains uncertain, probably involving several mechanisms, such as deterioration of the general health status, hypersensitivity of drugs used for COVID-19 treatment, stress, immunosuppression, vasculitis, and hyper-inflammatory response secondary to SARS CoV-2 infection as predisposing factors ( 45 47 ).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the present report, a large ulcer was also found on Cat-1's tongue base at the time of presentation, which may have contributed to inappetence. Various oral manifestations of COVID-19 have been reported in human patients, including dry mouth, gustatory impairment, gingivitis, sialadenitis, vesicular and ulcerative mucosal lesions predominantly located on dorsal surface of the tongue (as in our case), hard palate, and labial mucosa ( 45 47 ). The exact pathogenesis of such oral signs remains uncertain, probably involving several mechanisms, such as deterioration of the general health status, hypersensitivity of drugs used for COVID-19 treatment, stress, immunosuppression, vasculitis, and hyper-inflammatory response secondary to SARS CoV-2 infection as predisposing factors ( 45 47 ).…”
Section: Discussionmentioning
confidence: 53%
“…Various oral manifestations of COVID-19 have been reported in human patients, including dry mouth, gustatory impairment, gingivitis, sialadenitis, vesicular and ulcerative mucosal lesions predominantly located on dorsal surface of the tongue (as in our case), hard palate, and labial mucosa ( 45 47 ). The exact pathogenesis of such oral signs remains uncertain, probably involving several mechanisms, such as deterioration of the general health status, hypersensitivity of drugs used for COVID-19 treatment, stress, immunosuppression, vasculitis, and hyper-inflammatory response secondary to SARS CoV-2 infection as predisposing factors ( 45 47 ). In addition, high expression of ACE2, recognized as the SARS-CoV-2 entry ligand receptor, has been reported in cells of the oral cavity, predominantly in epithelial cells of the tongue, and in buccal and gingival tissues at a lesser extent, thus predisposing to oral SARS-CoV-2 infection with a local virus effect ( 48 ).…”
Section: Discussionmentioning
confidence: 53%
“…In fact, oral viral infections are common in clinical practice that are associated with oral lesions. Earlier studies have published some oral symptoms induced by SARS-CoV-2 infection, as for example ulceration and vesicular bullous lesions (20,21). In the oral mucosa, viral infections damage epithelial cells causing acute inflammatory response, presenting with solitary and multiple blisters or even ulcerations (22).…”
Section: Discussionmentioning
confidence: 99%
“…Dryness of the oral cavity can also be produced by mouth breathing, dehydration, and COVID-19 related medications. Severe halitosis has also been reported in COVID-19 patients [ 83 ]. Usually, this xerostomia is self-limiting and transient in nature.…”
Section: Oral Manifestations Of Covid-19 Infectionmentioning
confidence: 98%
“…Other authors have reported association of COVID-19 with irregular and aphthous like lesions; herpetiform or zosteriform lesions; generalized non-specific ulcerations; erosions on the tongue, palate, and labial mucosa; atrophic and hyperkeratotic patches on the tongue, gingiva, and palate; lesions resembling erythema multiforme; desquamative gingivitis; and angina bullosa-like lesions [ 83 ]. Similarly, petechiae, post-inflammatory pigmentation, and vesicular eruptions have also been described.…”
Section: Oral Manifestations Of Covid-19 Infectionmentioning
confidence: 99%